Application of nanoparticles for the enhancement of latent fingerprints - Sametband, Matias; Shweky, Itzhak; Banin, Uri; Mandler, Daniel; Almog, Joseph (Chem Commun (Camb)Chemical communications (Cambridge, England), 2007)
Two different types of nanoparticles dissolved in organic solution, gold stabilized by n-alkanethiols and CdSe/ZnS stabilized by n-alkane-amine, adhere preferentially to the ridges of latent fingerprints; the gold deposits catalyze silver electroless deposition from "Silver Physical Developer" (Ag-PD), an aqueous solution containing silver colloids stabilized by cationic surfactants, to form dark impressions of the ridge details; the hydrophobic capped gold nanoparticles significantly improve the intensity and clarity of the developed prints compared with Ag-PD alone; finger marks treated with CdSe/ZnS nanoparticles can be viewed directly, due to their fluorescence under UV illumination.[on SciFinder (R)]
MEDLINE AN 2007147255(Journal; Article; (JOURNAL ARTICLE))